Geosynthetic for Effective Geo-Solutions in Malaysia - CHAN CHEE MING (Penerbit UTHM, 2024)
This is a book which gathers the best practices and research endeavours from both industry and universities in Malaysia, to showcase the advances in design, construction, applications and testing of geosynthetics in the country. The 15 chapters present interesting technical innovations in the field, refinement of the understanding in geosynthetic-soil interaction and mechanisms, as well as geo-environmental troubleshooting and solutions. This inaugural Technical Compilation by MyIGS aims to serve as a useful guide and reference for practitioners, researchers and academics alike, to position the effective use of geosynthetics for the present, and into the future.